POLA KEMITRAAN PEMASARAN LOBSTER DI KOTA BENGKULU - Romdhon, M. Mustopa; Sukiyono, Ketut (Jurnal AGRISEP, 2011)
Relationship among lobster marketing agents could determine partnership pattern, but how the relationship was build and run, its need depth explanation. The research was aims to synthesize partnership pattern, rights and obligations among agents under lobster marketing at Bengkulu Municipal. The Partnership pattern was explained descriptively through non-contractual, equipment and capital achieved. The research was employed at North Bengkulu Districts at three villages (Pasar Pedati, Pasar Ketahun and Pasar Seblat). They were biggest lobster supplier to the UD. Edi Koto. Respondents were fisherman under an unit fishing boat (32 unit) and 12 traders. The results showed that partnership pattern among agents were KOA and Dagang Umum where was KOA more dominant than dagang umum and its profitable.